Tingkat Pengetahuan Ibu Tentang Pemberian MP-ASI Di Desa Ngunut Jumantono Karanganyar - Ernawati Ernawati (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Keywords: Level Of Knowledge, Provision Of Complementary Feeding. Keberhasilan granting MP BREAST MILK is influenced by a variety of factors, one of which is the level of knowledge. Results of a survey in village Jumantono Ngunut septi Karanganyar by conducting interviews with midwives, the village that the knowledge of the mother in each village in giving BREAST MILK to her baby to varied valid any know about giving MP ASI but there are some mothers who are less knowledgeable about granting MP ASI. The goal in this research is to know the level of knowledge about giving mom MP ASI in the village Jumantono KaranganyarJenis Ngunut this research is quantitative descriptive. The population of this research is all mothers who have babies in the village Jumantono Ngunut Karanganyar. Research on a sample is the mother who has toddlers aged 0-2 years in the village of Jumantono Ngunut Karanganyar totaling 72 respondents. This instrument is used in is the questionnaire. Data processing stages: cleansing, coding, scoring, insert, data analysis that is used in is a frequency distribution and percentage of a variable. The results of the research note that the characteristics of the respondents based on level of education ELEMENTARY education level prevailing majority of 23 respondents (31.9%) with enough knowledge level as many as 20 respondents (87,0%). Characteristics of respondents based on majority parity are parity 1 applies 35 respondents (48.6%) with enough knowledge level as much as 28 respondents (80,0%). Characteristics of respondents based on the age of majority age of 21-35 years as many as 67 respondents (93,1%) with enough knowledge level as much as 52 respondents (77,6%). The characteristics of respondent based on the work of the majority is a Housewife (IRT) as much as 40 respondents (55,6%) with enough knowledge level as much as 87.5 of respondents (35%). Summary of the research knowledge about giving mom MP ASI in the village Jumantono Ngunut Karanganyar largely had enough knowledge level of 57 respondents (79,2%)